BS EN ISO 11890-2 AMD 1. Paints and varnishes. Determination of volatile organic compounds(VOC) and/or semi volatile organic compounds (SVOC) content. Part 2. Gas-chromatographic method (19th June 2023) - British Standards Institution,
No abstract available